CREATION AND IMPLEMENTATION OF THE ELASTIC ELEMENTS OF THE INTERMEDIATE BONDING THE TRACK - Hovorukha, V. V. (Science and Transport Progress, 2003)
The development problems of a rail transport and heightening of a technological level of a construction of an intermediate rail fastening are considered.